NMR and DFT Study of the Copper(I)‐Catalyzed Cycloaddition Reaction: H/D Scrambling of Alkynes and Variable Reaction Order of the Catalyst. Issue 10 (29th April 2016) - Kalvet, Indrek; Tammiku‐Taul, Jaana; Mäeorg, Uno; Tämm, Kaido; Burk, Peeter; Sikk, Lauri
Abstract: Mechanism of an efficient and easily applicable catalytic system for the copper(I)‐catalyzed azide–alkyne cycloaddition (CuAAC) reaction, consisting of phosphane‐ligated Cu I carboxylates and apolar/aprotic solvent was investigated by means of 1 H NMR reaction monitoring techniques, isotope exchange studies, and DFT calculations (at the M06L/6‐311++G(d, p)//B97D/cc‐pVDZ (SDD) level of theory). Kinetic analysis indicates 1st order kinetics with respect to [Azide] and nonlinear positive order in [Cu]. H/D scrambling between alkynes reveals a quickly reached equilibrium existing between Cu I –carboxylates and Cu I –acetylides and that proton transfer processes are mediated by acetate/acetic acid system. According to the computational results, the Cu–triazolide forms a dinuclear structure that equalizes the copper atoms in the catalytic complex. Abstract : Complex reaction orders : The mechanism of the copper(I)‐catalyzed cycloaddition reaction, catalyzed by phosphane‐ligated Cu I ‐carboxylates in an apolar/aprotic solvent, is studied by using experimental and computational methods. The results support the mononuclear proton‐transfer pathways: alkyne deprotonation and Cu–triazolide protolysis, mediated by carboxylate base.